EXPRESSION OF TOLL PROTEIN GENE IN TISSUES OF TIGER SHRIMP (PENAEUS MONODON) EXPERIMENTALLY EXPOSED TO VIBRIO HARVEYI - A.UMA; A.H.M. HARRESH; G.REBECCA (International Journal of Pharma and Bio Sciences, 2012)
Toll protein is an important non-specific immune protein in crustaceans which rely on innate immunity. The expression of Toll protein gene was studied in healthy and experimentally exposed (Vibrio harveyi) Penaeus monodon (tiger shrimp) by reverse transcriptase polymerase chain reaction (RT-PCR) using self-designed Toll-specific PCR primers. Comparison of the expression profiles of Toll protein gene in gills, hepatopancreas and gut of P.monodon showed that experimental exposure to a gram-negative bacterial pathogen, Vibrio harveyi induces Toll protein gene expression in these organs. The identity of the PCR amplified P.monodon Toll protein gene was confirmed by nucleotide sequencing and analysis